Al-Islam dan Kemuhadiyahan (AIK) Pilar Dakwah Islam Rahmatan Lil Alamin (Studi Pada Perguruan Tinggi Muhammadiyah di NTT) - Muhammad Tamrin (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2019)
Al-Islam and Kemuhammadiyahan (AIK) are part of the Muhammadiyah curriculum which teaches about Islam and religion in students who study at Muhammadiyah educational institutions, to introduce Islam and Muhammadiyah. In Muslim students, AIK teaches Islamic values ​​to be understood, internalized, and practiced to make it a way of life, both personal and community life. While AIK for non-Muslim students introduces Islam and the universal values ​​contained therein (Islam Rahmatan Lil Alamin). In the East Nusa Tenggara region there are 3 Muhammadiyah Universities with a number of non-Muslim dominated students. The three colleges are in Alor Regency, Sikka District, Maumere and Kupang City. In this study took 2 locations, the majority of which were non-Muslim students. First, the Muhammadiyah Maumere Teachers' Training College is in the majority area of ​​the Catholic community and the second Muhammadiyah Kupang University, the majority of which are Protestant. Both of these Universities are experiencing significant progress day by day on physical development and the number of students. This study aims: 1) To find out about the AIK curriculum and the Teaching Pattern for non-Muslim students; 2) To find out the response of students about the existence of AIK courses. The type of research used in this research is field research with descriptive qualitative research methods using data collection techniques through interviews, observation, and documentation. The data analysis technique used is the interactive data analysis technique of Milles and Huberman models.